Evaluating the economic feasibility of anaerobic digestion of Kawangware Market Waste - Arati, James M. (Kansas State University, 2009)
Anaerobic digestion is an alternative solution to organic waste management that offers economic and environmental benefits. The Kawangware open air market in Kenya generates approximately 10 metric tons of organic waste per day as a result of farm produce sold at the market. Fresh fruits and vegetables sold at the market account for more than 80 percent of the organic waste. This organic waste is left uncollected, piling up and therefore becoming pollution to the environment. Instead, this waste can be processed by anaerobic digestion to produce energy, organic fertilizer and greenhouse gas credits. The main objective of this project is to help investors and members of Kawangware Waste Utilization Initiative (a waste management community based organization in the Kawangware area) answer the following questions: (a) Is it economically profitable to invest in an anaerobic digestion system to convert the market organic waste to methane and fertilizer? (b) Is it economically profitable to burn the methane to generate electricity? To answer these questions, the study examines the costs and returns of producing methane, electricity, and fertilizer from organic waste under various scenarios using net present value, internal rate of return and payback period analysis techniques. Three production conditions under various scenarios using the anaerobic digester are examined. The conditions include: (a) Production of methane and organic fertilizer. (b) Production of methane, organic fertilizer, and carbon credits. (c) Production of electricity, organic fertilizer, and carbon credits. From these three production conditions examined, production of methane, organic fertilizer and carbon credits had the highest net present value of $332,610, internal rate of return of 21.4%, and the shortest payback period of 7.9 years. If carbon credits could not be sold the next best alternative would be production and selling of methane and organic fertilizer which has a net present value of $246,752, internal rate of return of 19%, and a payback period 9.2 years.
Keywords: Anaerobic Digestion; Organic Waste; Kenya; Net Present Value; Methane; Economics, Agricultural (0503)